Comparative efficacy of tyrosine kinase inhibitor treatments in the third-line setting, for chronic-phase chronic myelogenous leukemia after failure of second-generation tyrosine kinase inhibitors. Issue 1 (January 2015) - Lipton, J.H.; Bryden, P.; Sidhu, M.K.; Huang, H.; McGarry, L.J.; Lustgarten, S.; Mealing, S.; Woods, B.; Whelan, J.; Hawkins, N.
Highlights We compared the efficacy of ponatinib and 2G-TKIs in CP-CML after ≥1 prior 2G-TKI. Relevant studies were identified by systematic review. Estimated response to 2G-TKI was 22–26% versus 60% (95% CrI 52–68%) with ponatinib. Probability of response was greater with ponatinib than with a further 2G-TKI.